A system dynamics model for agriculture in Danube mouths region - Steliana Rodino (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
A dual challenge for the sustainable development of the Danube mouths region is the conservation of the natural ecological assets and the improvement of the quality of life for its residents. Aiming to offer support for regional sustainable policies for improvement of land sea synergies in the Coastal area of Romania, we have developed a system dynamics model for the development of agricultural sector in this region. The model scope is strongly linked to Farm to Fork strategy released by European Commission in 2020 as a response to the global challenges of providing access to healthy food, protect biodiversity and adapt to climate changes. The potential of our case study area for conversion to organic farming is closely related to the presence of protected areas on Tulcea territory. The system dynamics model is built so as to highlight that agricultural sector and the work of farmers is part of the solution not the problem, as we move towards transition to bioeconomy.
Keywords: Q15; Q5; 330; organic agriculture; Romanian coastal area; system dynamics